canoe encodes a novel protein containing a GLGF DHR motif and functions with Notch and scabrous in common developmental pathways in Drosophila. - Miyamoto, H.; Nihonmatsu, I.; Kondo, S.; Ueda, R.; Togashi, S.; Hirata, K.; Ikegami, Y.; Yamamoto, D. (Genes & Development, 1995)
The canoemisty1 (cnomis1) mutation was isolated by virtue of its severe rough eye phenotype from approximately 500 fly lines, each harboring a single autosomal insertion of a P element (Bm delta w). Excision of the P element generated a lethal, null allele, cnomis10, together with many revertants with normal eye morphology. Ommatidia homozygous for cnomis10, produced in an otherwise wild-type eye by somatic recombination, typically contain a reduced number of outer photoreceptors. Some cnomis1 homozygous adults bear extra macrochaetes on the head, notum, humerus and/or scutellum. cnomis1 hemizygotes often show conspicuous wing phenotypes such as a notched blade and the loss of a cross vein. The sequence of cno cDNA clones isolated from an embryonic cDNA library revealed a long open reading frame that potentially encodes a 1893-amino-acid protein with the GLGF/DHR motif, a conserved sequence in Discs large, Dishevelled, and some other proteins associated with cellular junctions. Flies doubly mutant for cnomis1 and scabrous1 (sca1) and those for cnomis1 and the split (spl) allele of Notch (N) always have rumpled wings curved downward. The spl; cnomis1 double mutant flies also exhibit a "giant socket" phenotype. These phenotypes are rarely observed flies singly mutant for either cnomis1, sca1 or spl. The wing vein gaps caused by Abruptex1, a N allele producing an activated form of N protein, are dominantly suppressed by cnomis1. Heterozygosity for shaggy and myospheroid promotes formation of extra wing veins in cnomis1 homozygotes. The genetic interactions suggest that cno participates with members of the N pathway in regulating adhesive cell-cell interactions for the determination of cell fate.